Imperfect Decision-Making and the Tax Payer Puzzle - Dieter Schmidtchen; Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1997)
Even if the expected punishment on tax evasion is negligible, empirical studies show that actual tax evasion is smaller than rational choice models predict. In addition to this, tax payer do not respond on parameter changes as predicted. Some authors tried to explain this puzzle by assuming "tax morale". Our paper models tax payers as imperfect decision-makers and explains deviations from the optimal solution by making use of a weaker assumption: The imperfect tax payer's decision to deviate from a given rule depends on their competence and on the complexity of their situation.
Keywords: H26; K42; 330; tax compliance; bounded rationality; imperfect decision-making; detection skill; rule-governed behavior